2010
DOI: 10.1111/j.1365-2516.2010.02329.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in patients with haemophilia and high responding inhibitors: Izmir experience

Abstract: This report evaluates the haemostatic efficacy of recombinant factor VIIa (rFVIIa) and activated prothrombin complex concentrate (APCC) in patients with haemophilia and high responding inhibitors who underwent major and minor surgery. Data pertaining to surgeries from 2001 to 2009 at a single centre were retrospectively analysed. During this period, 53 surgical procedures were performed in 30 haemophiliacs with high responding inhibitors. Mean age was 16.2±9.4 years. Eleven major surgeries in 4 patients, 41 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…With the introduction of by ‐ passing agents, surgical interventions can be performed safely in haemophilia patients with inhibitors [18,19]. Any severe bleeding was not seen in our haemophilia patients with inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of by ‐ passing agents, surgical interventions can be performed safely in haemophilia patients with inhibitors [18,19]. Any severe bleeding was not seen in our haemophilia patients with inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Hemophiliacs with inhibitors had more bleeding complications and a longer period to healing [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…The bleeding in this patients could only be controlled on the 15th day after using intensive by-pass agent and 2 units of erythrocyte suspension had to be transfused because of bleeding. Ankaferd (blood stopper) was used in one patient (20)(21)(22)(23)(24). In a study by Zülfikar et al (25) where the authors shared their 11-year experience of hemophilic patients with inhibitor, bleeding could be controlled with difficulty in two patients who were circumcised.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies about circumcision experience in hemophilia patients with inhibitor. In the surgical experience of Balkan et al (20) in hemophilic patients with inhibitor, circumcision was reported in one patient. The bleeding in this patients could only be controlled on the 15th day after using intensive by-pass agent and 2 units of erythrocyte suspension had to be transfused because of bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation